Modelos de sobrevivência bivariados baseados na cópula PVF - Biondo, Thiago Ramos (Universidade Federal de São Carlos, 2020)
An alternative developed to study associations among multivariate survival times is the use of models based on copula functions. In this work, we use the survival model derived from the PVF copula, based on the Power Variance Function distribution, to model the dependence of bivariate data in the presence of covariates and censored observations. For inferential purposes, we perform a Bayesian approach using Monte Carlo Markov Chain (MCMC) methods. Some discussions about model selection criteria are presented. In order to detect influential observations, we used the Bayesian method of deletion influence analysis of cases based on divergence psi. Finally, we show the applicability of the proposed models to simulated and real datasets.
Bivariate survival models based on PVF copula
Keywords: Análise de sobrevivência; Funções cópulas; Cópula PVF; Inferência bayesiana; Simulação; Survival analysis; Copula functions; PVF copula; Bayesian inference; Simulation; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE MULTIVARIADA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::FUNDAMENTOS DA ESTATISTICA